Calls to helplines in Australia following media reports of Robin Williams' suicide. Issue 6 (24th July 2020) - Pirkis, Jane; Currier, Dianne; Too, Lay San; Bryant, Marc; Bartlett, Sara; Sinyor, Mark; Spittal, Matthew J.
Abstract: Objective: In the United States, there was an increase in calls to helplines following media reporting of Robin Williams' suicide. We aimed to determine whether this was the case in Australia. Method: The helpline services Lifeline and Beyond Blue provided us with weekly data on calls received for 2013–2015. We conducted interrupted time series regression analyses to determine whether there was an increase in the average weekly number of calls received by each helpline in two periods after the story about Williams' suicide broke (1 week and 4 weeks). Results: We found strong evidence of an increase in calls to Lifeline (incidence rate ratio [IRR] =1.13; 95% confidence interval [CI] =1.02–1.25; p = 0.016) and Beyond Blue (IRR = 1.32; 95% CI = 1.09–1.59; p = 0.004) in the week after Williams' suicide was first reported. We found no evidence of higher than normal call volumes for Lifeline (IRR = 1.04; 95% CI = 0.99–1.10; p = 0.104) or Beyond Blue (IRR = 1.10; 95% CI = 1.00–1.22; p = 0.058) over the four weeks following Williams' death, however, suggesting that calls leveled out over this period. Conclusion: Suicide prevention experts and media professionals must work together to minimize the negative impacts of reports on suicide and maximize their positive ones. In cases where the story is likely to receive extensive international coverage, it may be important for local media to encourage help‐seeking.